Minichromosome maintenance expression defines slow-growing gastroenteropancreatic neuroendocrine neoplasms - Schimmack, Simon; Lawrence, Ben; Kenney, Barton; Schmitz-Winnenthal, Friedrich Hubertus; Modlin, Irvin M.; Kidd, Mark (Translational oncology, 2016)
Small intestinal neuroendocrine neoplasm (SI-NEN) proliferation is quantified by Ki67 measurements which capture G1-G2M phases of the cell cycle. G0 and early G1 phases, typical of slow-growing cells, can be detected by minichromosome maintenance protein (MCM) expression. We hypothesized that these replication licensing markers may provide clinically relevant information to augment Ki67 in low-grade neuroendocrine neoplasia.